Evaluation of depression, self-esteem and hopelessness in patients admitted to psychiatry outpatient clinic in geriatric population during COVID-19 outbreak - Yildiz, Sevler; Kılıçaslan, Aslı Kazğan; Kurt, Osman; Uğur, Kerim (My University, 2021)
Infection control measures taken to ensure social isolation during the COVID-19 pandemic process seem to negatively affect the mental health of elderly individuals. In this study, it is aimed to examine the effects of pandemic on the mental health of the elderly. 150 patients over the age of 65 who were admitted to the psychiatry outpatient clinic for the first time during the pandemic period were included in the study. Socio demographic data form, Geriatric Depression Scale (GDS), Beck Hopelessness Scale (BHS), Rosenberg Self Esteem Scale (RSE) were applied to all cases after the psychiatric interview conducted by us. In the geriatric population, it was observed that there was a significant negative correlation between BHS and RSE (r = -0.241 p = 0.003), and a positive significant relationship between BHS and GDS (r = 0.478 p <0.001). There was no significant correlation between RSE and GHS (r = -0.042 p = 0.614). During the COVID-19 pandemic, it is understood that the hope level and self-esteem of the geriatric population are low, and their mood is depressive. Among the measures to be taken during infection control, we think that elderly people should be given psychosocial support, and thus a healthier environment can be offered to these individuals in terms of physical and mental aspects.
Keywords: Genel ve Dahili Tıp; Geriatri ve Gerontoloji; Psikoloji